Customer Loyalty and Customer Retention: Trend Required Today - Pierrend Hernández, Sara Delfina Rosa (2020)
The stable operation of the company depends directly on its market power. For this it is important to have a high degree of customer loyalty and if they are not satisfied with what is acquired it is important that the company has the ability to reverse it. However, there is no clear delimitation of both concepts (customer loyalty and retention) and that is the main objective of the article, as it is important that companies have a clear idea about the meaning of these. With its main function that effective policies are applied so that customers generate positive opinions about the company and come to influence the purchase decision of new individuals who do not have a clear idea of the company, where they go to meet their need and transmit The feeling of security that fails to meet expectations and the company is willing to correct this situation.